Evaluation of California bearing ratio of Kuantan clayey soils stabilized by recycled and reuse material mixed with portland cement - Syed Muhammad , Syed Kamil (2013)
California Bearing Ratio (CBR) test is a common test that had been used especially in Highway Engineering to find the soft sub-grade strength in pavement design. But most civil engineer always faced difficulties in obtained suitable soil stabilization to make the soft sub-grade have high CBR value. The main objective of this study is to evaluate the California Bearing Ratio (CBR) of the Kuantan clayed soil and to select the most suitable additive that can-be used as soil stabilization. In this study there are two phases of the laboratory testing which phase one is engineering properties of the soil. From this test we will get the plastic limit (PL), liquid Limit (LL), and plasticity index (PT) of the soil. In this phase also the sieve analysis of the soil is carried out. For the phase one, all the data will be compared and referred to the AASHTO and USCS standard as a guideline. The California Bearing Ratio (CBR) test will be carried out on phase two. In this phase, the procedure of the California Bearing Ratio (CBR) test procedure will be referred to BS 1277-4 1990 standard. From CBR test we will get the average CBR value needed to evaluate and compare with others in order to select the highest CBR value that can be recommended to be used as additive to the soil sample.